Do inflation and high taxes increase bank leverage? - Per Hortlund (Stockholm School of Economics, The Economic Research Institute (EFI), 2005)
Does the combination of inflation and high corporate taxes explain the increase in bank leverage in the 20th century? Inflation automatically increases bank debt, while high corporate taxes hinder capital accumulation. Capital ratios therefore drop, until leverage-induced returns are sufficient to uphold them at constant levels. This theory was confronted with Swedish bank data 1870-2001. Bank capital ratios dropped when inflation and corporate tax rates were high, during WWI and in 1940-1980. The theory can explain the sinking bank capital ratios during these periods, but also their relative stability since the early 1980s. High corporate taxes and inflation were estimated to account for half of the drop in Swedish bank capital ratios since WWII.
Keywords: E44; E52; G28; G32; H25; N23; N24; 330; Bank leverage; Capital-asset ratio; Inflation; Corporate taxes; Bank; Bankgeschichte; Eigenkapital; Inflation; Unternehmensbesteuerung; Schweden